UNLOCKING THE DRIVE TO LEARN: NAVIGATING INDIVIDUAL, FAMILIAL, AND EDUCATIONAL DYNAMICS OF COGNITIVE ENGAGEMENT IN UNIVERSITY STUDENTS - Deng, Wenzhe (PUPIL: International Journal of Teaching, Education and Learning, 2024)
This research paper explores the multi-dimensional factors influencing cognitive engagement among university students in Shanghai, integrating individual, familial, and institutional dynamics. Utilizing a mixed-methods approach, the study draws on data from the "China College Student Survey (CCSS)" to measure cognitive engagement through a specifically designed Likert scale. The study sample consists of 1,452 valid responses from 1,600 distributed questionnaires across six universities. Through descriptive statistics, correlation, and regression analyses, the research identifies significant determinants of cognitive engagement. Key findings indicate that cognitive engagement is profoundly influenced not only by individual characteristics—such as holding leadership positions—but also by familial factors like parental education and social networks, as well as comprehensive institutional factors including teaching quality and university infrastructure. Notably, urban-rural backgrounds and family economic conditions emerge as significant moderators, affecting how institutional and familial inputs influence students’ cognitive engagement. Results underscore the critical role of tailored educational strategies and supportive familial and institutional environments in enhancing cognitive engagement. The research contributes to educational theory by providing empirical support for the integration of multi-dimensional factors in understanding student engagement, offering actionable insights for educational policy makers and institution administrators aiming to foster enriched learning environments.